Complete guide to prescription & nonprescription drugs, 2010 - Griffith, H. Winter (Henry Winter), 1926-1993.; Moore, Stephen W.; Boesen, Kevin; Boesen, Cindy (New York : Penguin Group, 2009)
Revised and updated, this classic bestseller provides the necessary information about all the prescription and nonprescription drugs that the public has come to rely on. This reference covers 5,000 brand-name drugs and 700 generic drugs.
"Includes: revised information on new FDA changes; easy-to-use chart format for quick access to data; guidelines to avoid dangerous interactions; information on dangerous side effects; warnings and vital data for safe use; more than 6,000 brand names and 1000 generic names"--Cover.
"A Perigee book"
Includes index.
Keywords: Drugs; Drugs, Nonprescription